Perancangan Sistem Informasi Absensi Berbasis Website Menggunakan Model Pengembangan Waterfall - Gilang Perdana; Damars Alfi Syahri; Chairina Fachrunnida; Wasis Haryono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Employee PT TRAFINDO PRIMA PERKASA is a company engaged in the medium voltage electrical equipment industry. The employee attendance system currently in place at PT TRAFINDO PRIMA This is still done manually, starting from recording employee entry times, recording employee exit times to making employee attendance reports. Therefore, during the recording process, there is a possibility of errors, or the resulting report is less precise and slow in finding the required data. The research method applied is the waterfall method. This employee attendance information system is web-based. With this application, the attendance information system will be better than the manual system, so that it can operate more effectively and efficiently, and this system will be more supportive and improved when compared to the previous system. In addition, the best solution is to use a computerized system that can solve various problems in this company, to support activities within the company.